"Chudo nevedomoi sily": Public Literary Readings in the Era of the Great Reforms. Issue 1 (January 2014) - VASSENA, RAFFAELLA
<x xml:space="preserve">Abstract</x> Up to the first half of the nineteenth century, Russian poets and literati read their own works aloud mainly at private literary circles or in the drawing rooms of the aristocrats where musical and literary evenings were held for an elite audience. At the beginning of the 1860s, new forms of "public readings" arose. On these occasions literati, musicians, and singers with varying degrees of fame performed in front of a paying public. The first part of this article looks at the salient phases of the roots of public readings at the start of the 1860s and the political and social events which marked their development, while the second part examines the evolution of this phenomenon, and its subsequent decline, over the next two decades, noting how public readings carried different meanings for different parties: the masses regarded them as a symbol of the freedom of expression that the state's reform package failed to include, inserting meaning into the readings that writers often did not intend, and that censors had not anticipated. Writers, meanwhile, welcomed a new opportunity to connect with a broader audience and tap into the growing commercialization of literature through journalism. Conceived in part as a way to exert an aesthetic and moral influence upon the attending masses, public literary readings would instead make their most significant impact in the social and political spheres.